2016
DOI: 10.1073/pnas.1606444113
|View full text |Cite
|
Sign up to set email alerts
|

Global phosphoproteomic profiling reveals perturbed signaling in a mouse model of dilated cardiomyopathy

Abstract: Phospholamban (PLN) plays a central role in Ca2+ homeostasis in cardiac myocytes through regulation of the sarco(endo)plasmic reticulum Ca 2+ -ATPase 2A (SERCA2A) Ca 2+ pump. An inherited mutation converting arginine residue 9 in PLN to cysteine (R9C) results in dilated cardiomyopathy (DCM) in humans and transgenic mice, but the downstream signaling defects leading to decompensation and heart failure are poorly understood. Here we used precision mass spectrometry to study the global phosphorylation dynamics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
(45 reference statements)
6
29
1
Order By: Relevance
“…Hence, the downregulation of this gene in SHRs being fed with HS diet seem to corelate with the development salt-sensitive HPN. Furthermore, this gene was also found in kidney transcriptome as well as haemoglobin where both studies were related to HPN (Marques et al, 2017;Zhang et al, 2014), and it has also been reported that Pi4k2a act via WNT-signaling pathway (Kuzmanov et al, 2016).…”
Section: Paraventricular Nucleus (Pvn)mentioning
confidence: 72%
“…Hence, the downregulation of this gene in SHRs being fed with HS diet seem to corelate with the development salt-sensitive HPN. Furthermore, this gene was also found in kidney transcriptome as well as haemoglobin where both studies were related to HPN (Marques et al, 2017;Zhang et al, 2014), and it has also been reported that Pi4k2a act via WNT-signaling pathway (Kuzmanov et al, 2016).…”
Section: Paraventricular Nucleus (Pvn)mentioning
confidence: 72%
“…Two-week post LAD induced MI hearts were induced and isolated as described previously 54 . Finally, 16-week-old PLN R9C mutant mice, a model of human DCM were analyzed as described 55 .…”
Section: Methodsmentioning
confidence: 99%
“…Generally, HF dys is hyper-phosphorylated by Ser/Thr kinases compared to Con and CRT hearts, which agrees with previous studies that suggest broad kinase activation and hyper-phosphorylation occurs during heart failure. [26][27][28][29] Importantly, CRT reduced and thus restored overall phosphorylation. While the clinical efficacy of CRT has been known for some time, it was nonetheless unexpected that it should reverse such a broad fingerprint of heart failure.…”
Section: Discussionmentioning
confidence: 99%